The interRAI Suite of Mental Health Assessment Instruments: An Integrated System for the Continuum of Care - Hirdes, John P.; van Everdingen, Coline; Ferris, Jason; Franco-Martin, Manuel; Fries, Brant E.; Heikkilä, Jyrki; Hirdes, Alice; Hoffman, Ron; James, Mary L.; Martin, Lynn; Perlman, Christopher M.; Rabinowitz, Terry; et al. (Frontiers in Psychiatry, 2020)
The lives of persons living with mental illness are affected by psychological, biological, social, economic and environmental factors over the life course. It is therefore unlikely that simple preventive strategies, clinical treatments, therapeutic interventions, or policy options will succeed as singular solutions for the challenges of mental illness. Persons living with mental illness receive services and supports in multiple settings across the health care continuum that are often fragmented, uncoordinated, and inadequately responsive. Appropriate assessment is an important tool that health systems must deploy to respond to the strengths, preferences and needs of persons with mental illness. However, standard approaches are often focused on measurement of psychiatric symptoms without taking a broader perspective to address issues like growth, development and aging; physical health and disability; social relationships; economic resources; housing; substance use; involvement with criminal justice; and recovery. Using conglomerations of instruments to cover more domain areas is impractical, inconsistent and incomplete while posing considerable assessment burden. interRAI mental health instruments were developed by a network of over 100 researchers, clinicians, and policy experts from over 35 nations. This includes assessment systems for adults in inpatient psychiatry, community mental health, emergency departments, mobile crisis teams, and long-term care settings, as well as a screening system for police officers. A similar set of instruments is available for child/youth mental health. The instruments form an integrated mental health information system because they share a common assessment language, conceptual basis, clinical emphasis, data collection approach, data elements, and care planning protocols. The key applications of these instruments include care planning, outcome measure, quality improvement and resource allocation. The composition of these instruments and psychometric properties are reviewed, and examples related to homeless are used to illustrate the various applications of these assessment systems.